2016
DOI: 10.1016/j.appet.2016.04.042
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal psychosocial characteristics on infant feeding styles

Abstract: Maternal feeding styles in infancy and early childhood are associated with children’s later risk for overweight and obesity. Maternal psychosocial factors that influence feeding styles during the complementary feeding period, the time during which infants transition from a milk-based diet to one that includes solid foods and other non-milk products, have received less attention. The present study explores how maternal psychosocial factors—specifically self-esteem, parenting self-efficacy, parenting satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…This finding is consistent with previous literature reporting positive associations between higher infant dietary quality and maternal age , education , income , and marital status and negative associations with maternal BMI . These sociodemographic risk factors have also been linked to nonresponsive feeding practices . Early intervention to promote RP among families with higher sociodemographic risk may improve dietary intake among at‐risk infants and help to moderate risk for obesity.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with previous literature reporting positive associations between higher infant dietary quality and maternal age , education , income , and marital status and negative associations with maternal BMI . These sociodemographic risk factors have also been linked to nonresponsive feeding practices . Early intervention to promote RP among families with higher sociodemographic risk may improve dietary intake among at‐risk infants and help to moderate risk for obesity.…”
Section: Discussionsupporting
confidence: 91%
“…A study with160 mothers of children between 3-18 months that evaluated psychosocial determinants in the maternal styles of feeding, demonstrated that self-esteem and obesity were significantly associated with pressure and restriction on feeding their children [8].…”
Section: Discussionmentioning
confidence: 99%
“…These, can be defined as responsive or sensitive when considered positive, and non-responsive when infused with authoritarianism, passivity or restrictions [5,6]. A non-responsive style was associated with a lower stimulation of healthy food choices by children, as well as, a worse infant's regulation of hunger and satiety [7,8]. Thus, the dietary parental style of complementary feeding may be associate with malnutrition and overweight in childhood, and obesity and metabolic syndrome for a lifetime [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that control over personal earning was a form of self-efficacy. Mothers with self-efficacy were positively associated with adequate feeding practice (Barrett, Thompson, & Bentley, 2016), as implied by Belsky's parenting model. Legal asset ownerships did not have an independent effect on adequate feeding practice.…”
Section: Discussionmentioning
confidence: 86%